Acoustic Emission Characteristics and Failure Mechanism of Fractured Rock under Different Loading Rates - Yongzheng Zhang; Gang Wang; Yujing Jiang; Shugang Wang; Honghua Zhao; Wenjun Jing (Shock and Vibration)
To study the loading rate dependence of acoustic emissions and the failure mechanism of fractured rock, biaxial compression tests performed on granite were numerically simulated using the bonded particle model in Particle Flow Code (PFC). Uniaxial tests on a sample containing a single open fracture were simulated under different loading rates ranging from 0.005 to 0.5 m/s. Our results demonstrate the following. (1) The overall trends of stress and strain changes are not affected by the loading rate; the loading rate only affects the strain required to reach each stage. (2) The strain energy rate and acoustic emission (AE) events are affected by the loading rate in fractured rock. With an increase in the loading rate, AE events and the strain energy rate initially increase and then decrease, forming a fluctuating trend. (3) Under an external load, the particles within a specimen are constantly squeezed, rotated, and displaced. This process is accompanied by energy dissipation via the production of internal tensile and shear cracks; their propagation and coalescence result in the formation of a macroscopic rupture zone.